Categorizing and Determining of BI-RAD Breast Cancer Score by Using Deep Learning Techniques - Azhar Kassem Flayeh; Ali Douik (Qubahan Academic Journal)
Breast cancer is second only to skin cancer in prevalence. Failure to detect and treat breast cancer early could be fatal. Breast cancer is more common in underdeveloped countries due to low health awareness and limited early detection methods. However, detecting equipment and radiography advances have helped solve this difficulty and suggest a drop in mortality. Along with ultrasounds, mammography, Magnetic Resonance Imaging (MRI), Computed tomography (CT) scan, and Positron emission tomography (PET) scans are used for diagnosis. These devices add data to test findings for greater accuracy. Diagnosticians determine breast cancer stage by examining tumor size, shape, and spread. Artificial intelligence users employ these factors as fixed values to classify the illness using region of interest (RIO), Gray Level Co-Occurrence Matrix (GLCAM), clustering, or mass constraints like diameter and volume. Artificial intelligence algorithms have created many techniques to extract features from massive volumes of data through training, such as deep learning. The study investigated DL algorithms (Attention mechanism and efficintNetB7 ) to determine the breast imaging-reporting and data system (BI-RADS) score by categorizing mammography images. The dataset Digital Database for Screening Mammography (DDSM) used in this study, acquired from Kaggle, contains 55,890 training samples, of which 86% are negative, and 14% are positive, categorized into classes C1, C2, C3, C4, and C5. This work utilized deep learning techniques and algorithms to accurately categorize breast cancer at 93%, 92%, 90%, and 93% for each category (C2, C3, C4, and C5). We developed the BI-RADS classifier model using the bycharm framework, an integrated development environment (IDE) for Python programming, and using multiple libraries, namely NumPy, Pandas, TensorFlow, Keras, Matplotlib, and Seaborn. This study used a laptop with the following specifications: an Intel Core i7 CPU, 16GB of RAM, and Intel RTX integrated graphics.